Relationship Between Cleanliness of the Home Environment with Incidence of Acute Respiratory Infections among Children Under Five Years - Tri Ratnaningsih; Eva Lusiana (Alta Dharma Publisher, 2020)
Acute Respiratory Infections (ARI) was the first cause of illness among children under five years. One of the factors that because ARI was the cleanliness of the home environment. The study aimed at the relationship between the cleanliness of the home environment and the incidence of Acute Respiratory Infections (ARI) among children under five years. The cross-sectional study design approach was applied in this study. Sixty-six samples were recruited by using the simple random sampling technique. The research instrument used a healthy home assessment form and a medical record of Acute Respiratory Infections (ARI) disease. Data analysis was using the Rho Spearman Test. The results of this study showed that most are classified as healthy houses, as many as 36 respondents (55%), and those who did not experience Acute Respiratory Infections (ARI) was 35 respondents (53.0%). The Spearman Rho test results showed that the value = 0,000 or <? (0,005) meant that there was a correlation between the cleanliness of the home environment and the incidence of ARI in children under five in the Pungging Health Center Pungging District, Mojokerto Regency. If the house were not healthy, the toddler would get sick more easily because an unhealthy house would store a lot of dust. It could trigger Acute Respiratory Infections (ARI), and vice versa, if the home were healthy, then the occupants would also feel comfortable and not susceptible to disease